A Carbohydrate Moiety of Secreted Stage-Specific Glycoprotein 4 Participates in Host Cell Invasion by Trypanosoma cruzi Extracellular Amastigotes - Florentino, Pilar T. V.; Real, Fernando; Orikaza, Cristina M.; da Cunha, Julia P. C.; Vitorino, Francisca N. L.; Cordero, Esteban M.; Sobreira, Tiago J. P.; Mortara, Renato A. (Frontiers in Microbiology, 2018)
Trypanosoma cruzi is the etiologic agent of Chagas disease. It is known that amastigotes derived from trypomastigotes in the extracellular milieu are infective in vitro and in vivo. Extracellular amastigotes (EAs) have a stage-specific surface antigen called Ssp-4, a GPI-anchored glycoprotein that is secreted by the parasites. By immunoprecipitation with the Ssp-4-specific monoclonal antibodies (mAb) 2C2 and 1D9, we isolated the glycoprotein from EAs. By mass spectrometry, we identified the core protein of Ssp-4 and evaluated mRNA expression and the presence of Ssp-4 carbohydrate epitopes recognized by mAb1D9. We demonstrated that the carbohydrate epitope recognized by mAb1D9 could promote host cell invasion by EAs. Although infectious EAs express lower amounts of Ssp-4 compared with less-infectious EAs (at the mRNA and protein levels), it is the glycosylation of Ssp-4 (identified by mAb1D9 staining only in infectious strains and recognized by galectin-3 on host cells) that is the determinant of EA invasion of host cells. Furthermore, Ssp-4 is secreted by EAs, either free or associated with parasite vesicles, and can participate in host-cell interactions. The results presented here describe the possible role of a carbohydrate moiety of T. cruzi surface glycoproteins in host cell invasion by EA forms, highlighting the potential of these moieties as therapeutic and vaccine targets for the treatment of Chagas disease.